Looking for religious logos in Singapore*. Issue 1 (1st January 2019) - Fischer, Johan
Abstract: Within the last couple of decades, new types of religious logos have emerged. Notably, halal (in Arabic, halal literally means "permissible" or "lawful") logos are increasingly appearing on products, certificates, websites as well as in restaurants, shops, and advertisements globally. However, little empirical attention has been paid to these religious logos as elements of visual systems, or to their effects. This article fills that gap. I argue that religious logos are not well understood theoretically, conceptually, or empirically and that they signify a new phase in logo development characterized by forms of religious regulation, certification, and standardization on a global scale. Building on empirical research on halal logos in Singapore, this paper shows that modern religious logos can fruitfully be explored at the interface between archive studies and ethnography.